Effectiveness of laser therapy over topical desensitising agents in the treatment of dentinal hypersensitivity-A systematic review - S, Dr. Shwetha; V, Dr. Chandra Sekhara Reddy; KM, Dr. Sudhir (International Journal of Scientific Research and Management (IJSRM), 2017)
AIM: To analyze the available scientific evidence on the effectiveness of laser therapy compared to thetopical desensitizing agents in the treatment of dentinal hypersensitivity.Materials and methods: A broad literature search was performed using both electronic database and handsearch. The databases like COCHRANECENTRAL, MEDLINE, GOOGLE SCHOLAR, EBSCO HOST,PROQUEST were used for online data search and hand search was performed in the central library of theinstitute to identify the relevant articles. Articles that satisfied the inclusion criteria with description ofrandomized clinical trials comparing lasers versus topical desensitising agents in the treatment of dentinalhypersensitivity were included. These included studies were subjected to critical analysis following theCochrane Collaboration tool for evaluating the risk of bias.Results: The initial search resulted in 65 articles; however, 31 of these articles were excluded because theywere duplicates and then 20 articles were excluded as they were not clinical trials. After analyzing the fulltext from 24 clinical trials, 17 were excluded because they did not fulfill all the selection criteria. Our finalreview included 7 studies. Of these 7 studies 1 study used Nd:YAG laser system, 4 studies used GaALASlaser, one study used Er:YAG laser and one study used both CO2 and Er:YAG laser. Among the sevenstudies 5 studies reported that the lasers alone or in combination with topical desensitising agents aresuperior over topical desensitising agents used alone. Remaining 2 studies reported that both lasers andtopical desensitising agents were equally effective in reducing dentinal hypersensitivity.Conclusion: With the constraints of limited available literature lasers alone or in combination with topicaldesensitising agents showed promising results than topical desensitising agent alone and this desensitizingefficacy of lasers was immediate and long lasting.Key words: Lasers, laser therapy, topical desensitising agents, effectiveness, dentinal hypersensitivity,systematic review